Bites by exotic snakes reported to the UK National Poisons Information Service 2009–2020. (2nd September 2022) - Jagpal, Pardeep S.; Williams, Hayley A.; Eddleston, Michael; Lalloo, David; Warrell, David; Sandilands, Euan A.; Thanacoody, Ruben; Gray, Laurence; Bradberry, Sally M.
Abstract: Introduction: Snakebite is recognised as a neglected tropical disease and a cause of substantial morbidity and mortality. Whilst the most medically important snakes are typically native of Asia, Africa, Latin America and Oceania, the possibility of encountering these snakes is no longer limited by geography due to an increasing number of exotic (non-native) snakes being held in captivity. Methods: A retrospective review of snakebite enquiries to the UK National Poisons Information Service (NPIS) between 2009 and 2020. Enquiries about the European adder ( Vipera berus) or where the identity of the snake was unknown were excluded. Results: There were 321 exotic snakebites in 300 patients involving 68 different species during this period. Ten patients were bitten on more than one occasion. The majority of patients (64.5%) were male. Most bites were inflicted by snakes of the family Colubridae (184/321, 57.3%); seventeen bites resulted in moderate symptoms (predominantly swelling of the bitten limb). There were 30 (9.3%) bites by Viperidae and 14 (4.3%) bites by Elapidae. All severe cases ( n = 15) resulted from bites by either Viperidae ( n = 10) or Elapidae ( n = 5). Antivenom was given in 17 cases. One fatality was recorded. Conclusions: Despite their low incidence, exotic snakebites present a substantial challenge for UK healthcare professionals. Although rare, these bites typically occur in individuals (usually male) who keep snakes as part of their occupation or hobby and are therefore at risk of multiple bites. Bites can result in venom hypersensitisation and the risk of venom-induced anaphylaxis. Rapid access to expert clinical advice is available in the UK on a 24-hour basis through the National Poisons Information Service and is strongly recommended in all cases of exotic snakebite.